Nomadic Education: A Panacea for Herdsmen and Farmers Conflicts in North Eastern Nigeria - Aide, Abdulrazak; Luka, Lawson; Shuaibu, Muawiya; Bello, Abubakar Umar (Kashere Journal of Politics and International Relations, 2023)
This study is designed to examine Nomadic Education as a panacea for Herdsmen and Farmers conflicts in North-Eastern Nigeria. Six research questions were formulated to guide the conduct of the study. The study adopted a survey research design where the target population for the study consist of the total number of Government officials and cattle herders and farmers in the North Eastern regions. Due to the large number of states in the North-Eastern Nigeria, the researchers sampled three states of Adamawa, Bauchi and Taraba as the sample states for the study. The researchers selected a sample of 1200 respondents from the three state using cluster sampling technique. Primary data for this study were collected using questionnaire to be developed by the researchers. The findings in the analysis shows that nomadic education has a role to play in tackling herdsmen and farmers clashes but despite the roles Nomadic education is playing in tackling the clashes between herdsmen and farmers, it is obvious that there are some factors militating against these efforts. It is based on this that that the following recommendations were put forward: Permanent and good school structure should be built for the children of the sedentary nomads having permanent settlement and the government should create an avenue for feedback from the people as regards any development on the programme as public opinion goes a long way in reporting daily events to the government who incidentally can make amend where necessary.